The Supremacy of the Dispute Settlement Mechanism (DSM) under the World Trade Organization (WTO) - Widiatedja, I Gusti Ngurah Parikesit (Brawijaya Law Journal, 2019)
The existence of inequality and poverty in some countries doubted the contribution of the WTO. The overwhelming spirit of national interest through the imposition of discriminatory and protective measures has deteriorated the WTO. Given its role for enforcing trade commitments, the dispute settlement mechanism is crucial to save the future of WTO. This paper aims to analyse the existence of the dispute settlement mechanism of WTO, whether it is still supreme in upholding the vision of trade liberalization. This paper argues that the supremacy of this mechanism has ensured the future of WTO by looking at two parameters. Firstly, it has a ruled-based character with a high level of legalism. Next, by looking at the decision of the Panel and the Appellate Body, the dispute settlement mechanism has effectively controlled the overwhelming spirit of national interest. This mechanism shows its supremacy by limiting the capacity of the WTO member states to impose discriminatory and protective measures, particularly related to public morals exception and cultural concern.